Investigating the effects of the Rho-kinase enzyme inhibitors AS1892802 and fasudil hydrochloride on the contractions of isolated pregnant rat myometrium. (July 2016) - Ergul, Merve; Turgut, Nergiz H.; Sarac, Bülent; Altun, Ahmet; Yildirim, Şahin; Bagcivan, Ihsan
Abstract: Objectives: Rho-kinases (ROCKs), are one of the dynamic structures of the actin cytoskeleton and they mediate different biological processes, including regulation of calcium sensitivity of smooth muscle contraction. The activation of Rho A/ROCK system is thought to be effective on the termination time of the pregnancy process. The aim of this study, was to investigate in vitro effects of the ROCK enzyme inhibitors, clinically available fasudil hydrochloride, and a new promising inhibitor AS1892802, on the contractions of isolated pregnant rat myometrium. Study design: Term pregnant Wistar albino rats ( n = 12), weighing 200–220 g, were used in this study. Myometrial tissues obtained from rats were dissected into four full-thickness longitudinal muscle strips and then myometrial tension was recorded isometrically. The inhibitory effects of cumulative concentrations of AS1892802 and of fasudil hydrochloride in the presence and absence of ODQ (guanylate cyclase inhibitor), l -NAME (nitric oxide synthase inhibitor) andl -NNA (endothelial nitric oxide synthase inhibitor) on oxytocin-induced myometrial contractions were measured, and values for −log10 EC50 (pD2 ) and mean maximal inhibition ( E max ) were compared. Results: Both ROCK inhibitors, AS1892802 and fasudil hydrochloride starting from the concentrations of 10 −6 M reached statistical significance on contraction amplitude and frequency of myometrial strips ( p < 0.05). The inhibition of the amplitude and frequency of myometrial contractions was antagonized with ODQ (10 −5 M; only amplitude), l -NAME (3 × 10 −5 M) andl -NNA (10 −5 M) ( p < 0.05). Conclusion: These results suggest that fasudil hydrochloride and AS1892802 may contribute to the development of new tocolytic drugs. We conclude that AS1892802 and fasudil hydrochloride perform this inhibitory effect partially through ROCK inhibition and the NO/cGMP pathway.